Personal growth of social educators in the age of information technology - Tuyakova, Ulbossyn; Baizhumanova, Bibianar; Mustapaeva, Talshyn; Alekeshova, Lyazzat; Otarbaeva, Zhansaya (International Journal of Evaluation and Research in Education (IJERE), 2024)
The study aims to develop an IT-based educational model for the personal development of a social educator: emotional intelligence (EI) and creative abilities. The study took place at L.N. Gumilyov Eurasian National University and K. Zhubanov Aktobe Regional University in Kazakhstan. It involved four moderators of online learning, 62 students majoring in “social pedagogy”; two of the teachers were members of the curriculum development commission. The study used the method of videoconferencing and inferential analysis to examine the relationship between EI and the creative abilities of future social educators in Kazakhstan. The results showed that the respondents had a moderate level of EI with an average value of 3.39. The correlation between EI and the creative abilities of social educators was medium-strong and positive. Results indicate that an increase in the level of EI leads to an increase in creative abilities. The novelty and originality of the study lies in the following aspects: the development of an educational model of personal growth of social pedagogues on the basis of information technologies taking into account EI and creative abilities; the use of innovative methods to study the relationship between EI and creative abilities of teachers demonstrates the use of modern technologies of data collection and identification of correlations between the studied variables, which indicates the importance of the development of EI and creative abilities of social pedagogues.